Cavitation phenomenon in mechanical prosthetic valves: Not only microbubbles. Issue 6 (16th May 2020) - Vriz, Olga; Arshi, Fatma; Ahmed, Mawada; Alhumaid, Mohammed; Galzerano, Domenico; Emmanual, Shisamma; Kinsara, Abdulhalim J.; Aladmawi, Mohammed; Alamro, Bandar; Alshahid, Maie; Pedrizzettid, Gianni
Abstract: Introduction: Microbubbles (MBs) or cavitation is high‐velocity, echo‐bright findings present during the closing or opening of a mechanical valve (MVP). Cavitation bubble growth or gas emboli are less frequently described. We evaluated the hemodynamic parameters involved in the formation of gas emboli and the impact of gas emboli on requests for additional investigations. Methods and Results: Transthoracic echocardiographic studies (TTE) of 57 patients (31 males, mean age 46.8 ± 13.8 years) with gas emboli were evaluated after heart valve replacement surgery. The majority (72%, n = 42) had a mitral or combined mitral/aortic MVP, with 28% (n = 16) an aortic MVP. The last TTE with and without gas emboli were considered for the same patient and the no emboli group was the control group (42 patients). The patient's blood pressure (BP) and heart rate (HR) were available for each TTE. Comparing the two TTEs, the systolic and diastolic BP, transmitral and aortic gradients, and left ventricular ejection fraction were similar but the HR (80.9 ± 18.7 vs 72.5 ± 13.9 bpm, P  = .02) was significantly higher in the group with gas emboli. A TEE was performed 52 times in 27 patients, due to gas emboli, with one case positive for thrombus/vegetation. For 19 patients, a brain CT was requested. In two patients, the indication for the brain CT was gas emboli but the result was negative. Conclusion: Gas emboli are frequently present and associated to an increased HR. They can cause the misdiagnosis of endocarditis or thrombus formation with significant additional requests for diagnostic examinations.